2020
DOI: 10.3390/membranes10120407
|View full text |Cite
|
Sign up to set email alerts
|

Discussion on Water Condensation in Membrane Pores during CO2 Absorption at High Temperature

Abstract: Water condensation is a possible cause of membrane wetting in the operation of membrane contactors, especially under high-temperature conditions. In this study, water condensation in pores of polytetrafluoroethylene (PTFE) hollow fiber membranes was investigated during high-pressure CO2 absorption around 70 °C. It was found that the liquid accumulation rate in the treated gas knock-out drum was constant during continuous operation for 24 h when all experimental conditions were fixed, indicating a stable degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…This mixture was used to mimic the composition of natural gas. The feed gas setup was constructed according to the method previously described by Chan et al [42].…”
Section: Methodsmentioning
confidence: 99%
“…This mixture was used to mimic the composition of natural gas. The feed gas setup was constructed according to the method previously described by Chan et al [42].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, as the operating temperature rises, the efficiency of removal decreases. Chan et al [28] studied the water condensation in pores of polytetrafluoroethylene (PTFE) hollow fiber membranes during high-pressure CO 2 absorption around 70 • C. They found that water condensation is a possible cause of membrane wetting in the operation of membrane contactors, especially under high-temperature conditions. Lim et al [29] numerically investigated the mass transport of one of a bundle of fibers using the ANSYS Fluent software that is based on the finite volume method (FVM).…”
Section: Introductionmentioning
confidence: 99%